2004
DOI: 10.1103/physrevlett.92.093903
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent Coincidence Imaging and Its Applicability in X-ray Diffraction

Abstract: Entangled-photon coincidence imaging is a method to nonlocally image an object by transmitting a pair of entangled photons through the object and a reference optical system respectively. The image of the object can be extracted from the coincidence rate of these two photons. From a classical perspective, the image is proportional to the fourth-order correlation function of the wave field. Using classical statistical optics, we study a particular aspect of coincidence imaging with incoherent sources. As an appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
310
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(320 citation statements)
references
References 28 publications
(38 reference statements)
3
310
0
1
Order By: Relevance
“…At present, it is generally accepted that both classical thermal light and quantum entangled beams can be used for ghost imaging and ghost diffraction, the only advantage of entanglement with respect to classical correlation may lie in the better visibility of information in photon counting regime. A lensless Fourier-transform ghost imaging scheme was proposed and its potential application in X-ray diffractive imaging has already been pointed out [17]. Another HBT type lensless ghost diffraction scheme with classical thermal light was also proposed [22], but no information about a pure-phase object diffraction pattern can be retrieved from its autocorrelation measurement, this makes the scheme unsuitable to X-ray diffractive imaging.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it is generally accepted that both classical thermal light and quantum entangled beams can be used for ghost imaging and ghost diffraction, the only advantage of entanglement with respect to classical correlation may lie in the better visibility of information in photon counting regime. A lensless Fourier-transform ghost imaging scheme was proposed and its potential application in X-ray diffractive imaging has already been pointed out [17]. Another HBT type lensless ghost diffraction scheme with classical thermal light was also proposed [22], but no information about a pure-phase object diffraction pattern can be retrieved from its autocorrelation measurement, this makes the scheme unsuitable to X-ray diffractive imaging.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The theoretical part of the lensless Fourier-transform ghost imaging scheme has been published in [17]. In Sec.Ⅱ the experimental setup and the pulsed pseudo-thermal source used in the experiment is briefly introduced.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…GI was originally performed using entangled photon pairs [2], and later on was realized with classical light sources [3,4,5,6]. The demonstrations of GI with classical light sources, and especially pseudothermal sources, triggered an ongoing e ort to implement GI for various sensing applications [4,7]. However, one of the main drawbacks of pseudothermal GI is the long acquisition times required for reconstructing images with a good signal-to-noise ratio (SNR) [1,8].…”
mentioning
confidence: 99%
“…This is done by correlating the intensities measured by the bucket detector with an image of the eld which impinges upon the object. GI was originally performed using entangled photon pairs [2], and later on was realized with classical light sources [3,4,5,6]. The demonstrations of GI with classical light sources, and especially pseudothermal sources, triggered an ongoing e ort to implement GI for various sensing applications [4,7].…”
mentioning
confidence: 99%
“…The first experiment was demonstrated with entangled light obtained from spontaneous parametric down conversion, 1 and the phenomenon was once considered as a characteristic of the nonlocality of entanglement, 2 hence the name "ghost" imaging was coined. Later, it was found that thermal light can also be used to realize GI, [3][4][5][6][7][8][9][10][11] which has many advantages as the source is readily available and has higher intensity so less data acquisition time is needed. However, a fundamental disadvantage is that there is always a large background, which restricts the maximum visibility to 1/3, compared to 1 for entangled light.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%